(untitled) (Revista de Estudos da Linguagem, 2005)
This paper is on children’s writing in the first stages of Brazilianelementary education. These data are considered in a relationshipbetween writing acquisition and speech acquisition, because similaraspects are noted in both process. Preliminary discussions areintroduced on an interpretation of writing data with someassumptions on Optimality Theory. At first, it seems possible tounderstand writing as a similar process to speech, but much researchis necessary. Seeing writing as a process is as important as what ithas to do with speech acquisition. It’s necessary to understandboth processes as attempte to achieve the standard and theseattempte also depend on cognitive and contextual factors.